2014
DOI: 10.1111/hae.12551
|View full text |Cite
|
Sign up to set email alerts
|

Bone disease in patients with haemophilia A and B – where are we now?

Abstract: It is evident that haemophilia A and B are associated with decreased bone mass in both adults and children. Decreased physical activity and vitamin D deficiency are some of the major factors leading to bone loss. Hepatitis C virus (HCV) infection may also contribute to low bone mineral density (BMD). However, definite conclusions regarding the exact prevalence and pathogenesis of osteoporosis cannot be conducted yet, due to the small sample size and significant heterogeneity among studies. Discordant findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…These differences may be partially attributed to the high prevalence of vitamin D deficiency worldwide [22] and small sample size [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences may be partially attributed to the high prevalence of vitamin D deficiency worldwide [22] and small sample size [23].…”
Section: Discussionmentioning
confidence: 99%
“…The attainment of optimum calcium intake and adequate vitamin D is significant [23]. El-Hajj et al [33] reported that a high dose of 2000 IU/day of vitamin D supplementation for 1 year increased bone area and bone mass in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Although low BMD is well described in PWH, data remains limited on fracture risk, with case series reporting fracture prevalence of 12% to 18%. [6][7][8] Osteoporosis is a pathologic bone disorder characterized by low BMD and microarchitectural bone disruption that results in increased risk for fracture. 9 The majority of studies investigating BMD in males with hemophilia have used areal BMD measurement by dual X-ray absorptiometry, which is unable to account for geometric differences affecting true volumetric BMD.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is known as haemophilic arthropathy or haemophilic joint disease (HJD) and it has a progressively negative impact on patients’ quality of life. Haemophilia is found to be associated with decreased bone mass in both adults and children [2]. Haemarthrosis, formed after repeated joint bleeds, could be prevented by providing prophylaxis to these patients by means of administering the missing CF from an early age and in a standard regimen.…”
Section: Introductionmentioning
confidence: 99%